Algorithm for covering circumferential wound on limbs with ALTP or/and DIEP flaps based on chain-linked design and combined transplantation. Issue 6 (June 2021) - Ou, Qifeng; Wu, Panfeng; Zhou, Zhengbing; Lei, Zeng; Pan, Ding; Tang, Ju-yu
Highlights: This is the first case series which detailedly discusses how to reconstruct the circumferential wound. The article elaborates how the wound is decomposed and how flaps are designed, by both pictorial illustration and concise language. The techniques are well-organized and corresponds with the wounds' size and shape. According to the flap availability on donor site and wound shape, the reconstructive algorithm has been classified into five subtypes, which bases mainly on the regularity and overall magnitude of width, but subtly generalizes most of the circumferential wounds. We are confident that the reconstructive surgeon would benefits from reading our research. Oblique split on circumferential wound and chain-linked flap design are the core of the whole algorithm. The oblique split on circumferential wound was intended to guide the flap be harvested in a shuttle shape, which can reduce the donor waste and facilitate the closure of the donor area. Meanwhile, the two ends of the flap form a closed-loop to perfectly match with the circumferential wound. With chain linked design, the shuttle-shaped flap can be extended enough to allows the head and tail being cross-arranged, so as to achieve partial widening and repair the circumferential wound with uneven width. At the same time. We integrate the chain-linked design into combined combination of two skin flaps. Similarly, each head of flap should overlap the tail, and the two flaps are placed diagonally on limb. But differently, the head of one flap are connected with the tail of the other, like a Gluttonous Snake. By ensuring those details above, the width on overlap section wound be technically broadened to be triple the width of one flap, which means as long as the width of the wound at this site is less than triple the width of one flap, full coverage can be successfully achieved. In summary, we proposed a cost-effective and practical algorithm to cover the circumferential wound, which achieve full coverage on extensive wound and meanwhile maintain primary donor-site closure. Abstract: Introduction: Coverage of circumferential wounds on limbs is a challenging reconstructive job. Here, we propose a skin flap-based algorithm to reconstruct circumferential wound with the chain-linked design and combined transplantation of ALTP and DIEP flap, which could achieve full-coverage and simultaneously primary donor-site closure. Patient and methods: From December 2007 to December 2018, 14 patients with circumferential would on upper or lower limbs underwent reconstruction with ALTP or DIEP flap, by the technique of combined transplantation or chain-linked design, or both. The wound was classified into five different types according to the width compared to the donor site (overall magnitudes and regularity), which was separately reconstructed by five different wound decomposition and corresponding flap design. Flap survivorship, complication on recipient or donor site and any secondary surgeries have been recorded. Results: 14 patients were successfully treated with 22 flaps, including seven patients reconstructed with one flap (4 bi-pedicled, 2 tri-pedicled), 6 patients reconstructed with two flaps (1 in mono-pedicled, 5 in multi-pedicled), one with 3 flaps and skin grafts. Only one donor site was not directly closed, and one experienced dehiscence but finally healed. All flaps survived uneventfully but three had minor edge necrosis and later treated with skin graft. Conclusion: The algorithm is practical in circumferential wound resurfacing on limbs for allowing flexible design, sufficient coverage, and low donor site morbidity.